Propisivačka praksa za liječenje vanbolničkih pacijenata sa dijabetesom tipa 2 u Centru tercijalnog nivoa u Džajpuru, Indija - Dadhich, Jaya; Dadhich, Devendra; Dadheech, Rajat; Gupta, Nivedita; Chandel, Ritesh; Kakkar, Shivankan (Scripta Medica, 2022)
Background: Over the last few years, an unexpected increase in the prevalence of diabetes in India have been witnessed. The present study was planned to analyse prescribing patterns of anti-hyperglycaemic drugs and assess the influence of Chief Minister’s Free Drug Scheme in Rajasthan, India. It aimed to evaluate, monitor and if possible, suggest modifications in prescribing practices to make medical care rational and also to assist minimising adverse drug reactions (ADRs).Methods: This was a cross-sectional, observational study carried out for a 12-month period. A total 400 known patients of type 2 diabetes mellitus (T2DM) from endocrinology outdoor of SMS Medical College Hospital (a tertiary care hospital in Jaipur, Rajasthan, India) were recruited and their prescriptions wereanalysed using the World Health Organization (WHO) prescribing indicators.Results: Most commonly observed age group was of 40-50 years (mean age 53.76 ± 8.84), with a male preponderance (57.5 %). Among them, 67.5 % of patients were found to be obese (mean BMI 29.79 ± 3.26). All anti-hyperglycaemic were prescribed in their generic names only. Metformin was the most frequently prescribed anti-hyperglycaemic agent. Among the fixed dose combinations, the most common was that of glimepiride and metformin (40.75 %), while most prescribed add on anti-hyperglycaemic was teneligliptin (51.5 %), followed by pioglitazone (30.5 %). A total of 53.25 % of these patients received insulin alongwith oral anti-hyperglycaemic agents.Conclusion: The anti-hyperglycaemic agent prescribing among endocrinology outpatients at tertiary care hospital in Jaipur was found to be satisfactory.